Spatially-resolved volume monitoring of adhesive cure using correlated-image optical coherence tomography - Ford, Helen D.; Tatam, Ralph P. (Elsevier Science B.V., Amsterdam., 2013)
Cross-correlation of optical coherence tomography (OCT) images has been applied to internal imaging of PVA and two-part epoxy adhesives during cure, providing information on relative viscosity at different positions within the sample volume. Spatial resolution of a few micrometres is obtained in the original OCT images, and a few tens of micrometres in the correlation images, enabling the progress of cure to be mapped in fine detail within a small cure volume. Evidence of phase separation is seen in the OCT and correlation images of a partially-cured PVA emulsion. Mixing structure and regions of poor cure can be observed in a poorly-mixed two-part epoxy.
Keywords: OCT, coherence tomography, cure-monitoring, adhesives